2016
DOI: 10.1177/003335491613100211
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Local Health Departments Associated with Implementation of Electronic Health Records and other Informatics Systems

Abstract: Objective. Assessing local health departments' (LHDs') informatics capacities is important, especially within the context of broader, systems-level health reform. We assessed a nationally representative sample of LHDs' adoption of information systems and the factors associated with adoption and implementation by examining electronic health records, health information exchange, immunization registry, electronic disease reporting system, and electronic laboratory reporting.Methods. We used data from the National… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
41
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 27 publications
0
41
0
1
Order By: Relevance
“…18 Readiness assessment, as a comprehensive measure in order to provide a proper image of existing conditions and the preparedness of healthcare organization to change, is also a way to identify potential causes of failure in innovation. 19 This study therefore aims to assess the readiness and associated factors among health professionals towardEMR implementation in the selected hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…18 Readiness assessment, as a comprehensive measure in order to provide a proper image of existing conditions and the preparedness of healthcare organization to change, is also a way to identify potential causes of failure in innovation. 19 This study therefore aims to assess the readiness and associated factors among health professionals towardEMR implementation in the selected hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…HIEs have demonstrated savings in health care costs [22,23], improvements in patient safety [24], workflow efficiencies [25], and improved data sharing among information systems and HIE participants [26]. HIEs are also stimulating structural and business process changes for PHAs [27,28]. An HIE has the potential to link EHR and laboratory data, providing PHAs with integrated, timely, consistently organized information that alleviates many challenges PHAs face in managing case reports.…”
Section: Introductionmentioning
confidence: 99%
“…Shah et al 30 indicated that both modifiable aspects, such as staffing and financial barriers, and non-modifiable aspects, such as geography, were highly associated with uptake of information systems. In addition, LHD characteristics, such as, length of tenure of top executive, having an information specialist on staff, and performing more clinical services were associated with the implementation of HIEs.…”
Section: Health Information Exchangementioning
confidence: 99%
“…In addition, LHD characteristics, such as, length of tenure of top executive, having an information specialist on staff, and performing more clinical services were associated with the implementation of HIEs. 30 Despite the challenges, EHRs and HIEs have the ability to improve care delivery and outcomes, and inform population health interventions and policy. 31 Although legislation has increased priority of health informatics in public health agencies, the literature suggests there are still barriers challenging the implementation of EHRs and HIEs.…”
Section: Health Information Exchangementioning
confidence: 99%